2020
DOI: 10.3390/membranes10040064
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Ozone Treatment on Ultrafiltration Performance and Nutrient Flow in a Membrane Based Nutrient Recovery Process from Anaerobic Digestate

Abstract: Membrane filtration of biological suspensions is frequently limited by fouling. This mechanism is well understood for ultrafiltration of activated sludge in membrane bioreactors. A rather young application of ultrafiltration is the recovery of nutrients from anaerobic digestates, e.g., from agricultural biogas plants. A process chain of solid/liquid separation, ultrafiltration, and reverse osmoses separates the digestate into different products: an organic N-P-fertilizer (solid digestate), a recirculate (UF re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 24 publications
(43 reference statements)
1
3
0
Order By: Relevance
“…In this way the process of purification of the liquid fraction of the digestate could be economically feasible resulted in the obtaining of several different products: an organic N-P-fertilizer (solid digestate), a recirculate (UF retentate), a liquid N-K-fertilizer (RO retentate) and water. Ozone treatment doesn't have any negative effect on the nutrient content of the digestate which also confirmed a study by [Gienau et al, 2020].…”
Section: Investigation Of the Dewatering Technologies Of The Digestatesupporting
confidence: 87%
“…In this way the process of purification of the liquid fraction of the digestate could be economically feasible resulted in the obtaining of several different products: an organic N-P-fertilizer (solid digestate), a recirculate (UF retentate), a liquid N-K-fertilizer (RO retentate) and water. Ozone treatment doesn't have any negative effect on the nutrient content of the digestate which also confirmed a study by [Gienau et al, 2020].…”
Section: Investigation Of the Dewatering Technologies Of The Digestatesupporting
confidence: 87%
“…The high CFV can enhance mass transfer phenomena and mitigate membrane fouling, but this leads to high operation costs and limits the economical application. In order to reduce the CFV requirement, Tobias et al [ 35 ] used ozone to pretreat anaerobic digestate, and they found that UF flux could be improved by 50–80% by ozonation. Ozone treatment reduced the biopolymer concentration and apparent viscosity.…”
Section: Resultsmentioning
confidence: 99%
“…Currently, new technologies for processing liquid fractions of digestates are still being explored [17]. One of the possibilities is through nutrient recovery such as struvite (STR) precipitation [18] and ammonia stripping (to produce ammonium sulphate (AS)) [6,[19][20][21], combined ozone treatment and ultrafiltration [22], combined system with aerobic granular sludge batch reactors and ultrafiltration [23], or utilizing fly ash as a chemical precipitant [24].…”
Section: Introductionmentioning
confidence: 99%